Linking food safety training with whistle-blowing: The mediation roles of job satisfaction and self-efficacy. Issue 1 (14th January 2019) - Yu, Heyao; A. Sirsat, Sujata; Neal, Jack A.
Abstract : Purpose: The purpose of this paper is to develop a validated food safety whistle-blowing scale and examine how training influences food handlers' whistle-blowing, the mediating roles of job satisfaction and food safety self-efficacy and the moderating roles of organization type and gender. Design/methodology/approach: A sample of 734 food handlers from the food service industry and 306 food handlers from the food processing industry were recruited. A two-step psychometric process was conducted to validate the scale, and a moderated mediation model was used to examine the mechanisms through which food safety training influences whistle-blowing. Findings: The results showed that job satisfaction and self-efficacy fully mediated the relationship between training and whistle-blowing. Organization type moderated the first step of the two indirect paths and gender moderated the second step, thereby supporting the mediated-moderated model. Practical implications: The results indicate the influence of food safety training programs on whistle-blowing behaviors and suggest other methods of enhancing employee whistle-blowing through human resource management. Originality/value: A validated scale is lacking to measure whistle-blowing in the food safety context, and little research has examined the influence of human resource practices on whistle-blowing. This study provides meaningful insights for researchers by developing and validating food safety the whistle-blowing scale, connecting training with whistle-blowing, and provides useful information for practitioners by offering the methods of enhancing whistleblowing in both the food processing and food service industry.